2023
DOI: 10.29333/iji.2023.16418a
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Moodle Learning Analytics on Students’ Performance and Motivation

Alwaely Suad,
Olga Tapalova,
Anna Berestova
et al.

Abstract: The central objective of this investigation was to study the issue of objectivity in assessing student performance using Moodle Learning Analytics system. It was decided to interview 532 students and 193 teachers concerning their attitude towards this grading system. This allowed analyzing the satisfaction of students and teachers with Moodle Learning Analytics, the objectivity of the grades given, the levels of students' motivation, students' readiness for self-education, the degree of mastery of theoretical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This, coupled with their ability to reduce paper consumption in educational contexts, makes them a potentially sustainable and effective alternative for learning. In addition, Suad et al [34] also noted increased levels of student motivation. Therefore, based on the findings of these authors, the use of LMSs not only enhances teaching practices through the ability to gather and analyze significant daily information, but also proves beneficial for students and current policies for a more sustainable world.…”
Section: Leveraging Tasks In Moodle To Enhance Active and Autonomous ...mentioning
confidence: 96%
“…This, coupled with their ability to reduce paper consumption in educational contexts, makes them a potentially sustainable and effective alternative for learning. In addition, Suad et al [34] also noted increased levels of student motivation. Therefore, based on the findings of these authors, the use of LMSs not only enhances teaching practices through the ability to gather and analyze significant daily information, but also proves beneficial for students and current policies for a more sustainable world.…”
Section: Leveraging Tasks In Moodle To Enhance Active and Autonomous ...mentioning
confidence: 96%
“…Many researchers have used TAM as (TEPE, 2022;Weng et al, 2018;Suad et al, 2023). According to (Chang et al, 2018;Lee et al, 2019) reported that the appropriate approach to examine the students' acceptance of VR technology in the educational setting is to expand the original TAM to include relevant factors to VR technology.…”
Section: Intention To Use Refers To the Individual's Intention To Use...mentioning
confidence: 99%